IT-Sicherheitsmanagement nach der neuen ISO 27001 : ISMS, Risiken, Kennziffern, Controls /: ISMS, Risiken, Kennziffern, Controls. ([2016]) - Kersten, Heinrich; Klett, Gerhard; Reuter, Jürgen; Schröder, Klaus-Werner
No abstract available